Tahsin Learning Practices for Mothers’ Qur’anic Reading Proficiency - Nevi Rizkia Yusuf; Dedi Masri (Academia Open, 2025)
General Background: The Qur’an serves as the primary guide for Muslims, requiring proper recitation in accordance with tajweed rules to preserve accuracy and meaning. Specific Background: In many non-formal Islamic education settings, such as taklim councils, mothers often possess basic Qur’anic literacy but lack proficiency in tajweed, with some remaining hijaiyah illiterate. Knowledge Gap: Limited research examines structured tahsin learning practices for adult women in rural Indonesian communities, particularly in non-formal institutions. Aims: This study investigates the implementation, methods, facilities, and challenges of tahsin Al-Qur’an learning at the Al-Hidayah Taklim Council, Punggulan Village. Results: Using qualitative descriptive methods with interviews, observations, and documentation, findings reveal that tahsin classes—held twice weekly—significantly improve participants’ reading fluency, letter recognition, and tajweed application through tailored methods (Iqra’ for beginners, Qiroati for advanced learners). Novelty: The research highlights adaptive instructional strategies in a non-formal, community-based female learning group, integrating individualized approaches within a collective setting to address diverse abilities and age-related challenges. Implications: The findings emphasize the potential of localized tahsin programs to strengthen Qur’anic literacy among women, thereby enhancing religious practice and intergenerational transmission of correct recitation skills. Highlights: Improves mothers’ Qur’anic reading and tajweed skills. Uses adaptive methods for diverse learner abilities. Strengthens community-based religious education. Keywords: Tahsin Al-Qur'an, Tajweed Learning, Taklim Council, Qur'anic Literacy, Non-Formal Education